FACTORS THAT INFLUENCE DELAY IN WORK COMPLETION TIME ON SELF-MANAGED PROJECTS - Elviyanti; Robby Hotter; Prenio Ahmad (Ikatan Dosen Menulis, 2024)
Construction activities carried out in a self-managed manner experienced several problems or obstacles. One of the problems faced is, among others, design changes, changes in material prices, details of costs carried out in the field are not included in the Cost Budget Plan, materials often arrive late from the work plan, work method errors which cause repetitive work, loss of tools and materials at the project location and are still completing the work after the work contract is completed, so this project experiences delays in completing the work even though the work contract has been completed. This research aims to find out what factors influence delays in completion and to find out the dominant factors that influence delays in completion of the project Self-Managed Vocational High School Padang Center of Excellence. This research was analyzed using descriptive statistical analysis methods to determine the dominant factors that influence delays in completing self-managed work. From the results of data analysis using descriptive statistical analysis, it was obtained that there were changes or additions to work during project implementation with factor code (B3) as the dominant factor influencing delays in completing self-managed work.